Does inflammation affect outcomes in dialysis patients?. Issue 4 (7th March 2018) - Nowak, Kristen L.; Chonchol, Michel
Abstract: Chronic, low‐grade inflammation is a common comorbid condition in chronic kidney disease (CKD), and particularly in chronic dialysis patients. In this review, we consider the question of whether inflammation affects outcomes in dialysis patients. Levels of proinflammatory cytokines, as well as C‐reactive protein, are elevated in chronic dialysis patients. Multiple factors likely contribute to chronic inflammatory activation in kidney disease patients including the uremic milieu, lifestyle and epigenetic influences, infectious and thrombotic events, the dialysis process, and dysbiosis. Increased inflammatory markers in both CKD and chronic dialysis patients are associated with adverse clinical outcomes including all‐cause mortality, cardiovascular events, kidney disease progression, protein energy wasting and diminished motor function, cognitive impairment, as well as other adverse consequences including CKD‐mineral and bone disorder, anemia, and insulin resistance. Strategies that have been shown to reduce chronic systemic inflammation in CKD and chronic dialysis patients include both pharmacological and nonpharmacological interventions. However, despite evidence that systemic inflammatory markers can be lowered in kidney disease patients treated with various strategies, evidence that this improves clinical outcomes is largely unavailable and represents an important future research direction. Overall, there is strong observational evidence that inflammation is high in chronic dialysis patients and that this is independently associated with numerous adverse clinical outcomes. Targeting inflammation represents a potentially novel and attractive strategy if it can indeed improve adverse outcomes common in this population.